Sasak Cultural Values to Improve Character of Islamic Primary School Students - Mardiyah Hayati; Niswatun Hasanah Nurdin; Shazy Abdelghany Ismail Ahmed (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2026)
Objectives: This research investigates internalization strategies, types of values, supporting factors, inhibiting factors, and the impact of Sasak cultural values to improve character of Islamic primary school students in Mataram, Indonesia. Method: A qualitative phenomenological approach was adopted and conducted at Sekolah Dasar (Islamic primary school) ‘Aisyiyah 1 Mataram, in Mataram City, Indonesia. Participants consisted of upper-grade students, classroom teachers, the school principal, and local traditional leaders selected through purposive sampling. Data were collected through participant observation, in-depth interviews, and document analysis. The data were analyzed using the interactive model proposed by Miles, Huberman, and Saldaña. Results: The findings indicate that the internalization of Sasak cultural values ​​occurs through structured morning activities, the integration of local folklore, teacher role modeling, and participation in community-based activities. Sasak cultural values ​​for character education include besiru (cooperation), bekelangan (empathy and social concern), pelungguh (ethical conduct), isin (moral restraint and self-awareness), and jari diri (positive personal behavior). Internalization of these values ​​is supported by strong school leadership, a conducive school environment, the active involvement of traditional community leaders, and parental engagement. Conversely, limited learning time and a lack of teacher understanding hinder the internalization process. Ultimately, Sasak cultural values ​​contribute to the development of students’ respectfulness, discipline, courtesy, responsibility, cooperation, self-regulation, and social sensitivity. Theoretical Contribution: This research contributes to the discourse on teaching the values ​​of ta'āwun (mutual assistance) and haya' (politeness) through culturally rooted Islamic education. Implication: These findings imply the importance of integrating local cultural values into character education within Islamic primary schools.